Crop Authenticity in Organic Horticulture: Insights from Recent Research and Practical Applications - Simona Fabroni; Luana Bontempo; Francesco Montemurro (Horticulturae)
For more than two decades, organic management has been associated with beneficial effects on human and soil health, while being environmentally sustainable due to the removal of/reduction in pesticides used as plant protection agents and chemical fertilizers [...]